Image‐guided percutaneous cryoablation of unresectable sacrococcygeal chordoma: Feasibility and outcome in a selected group of patients with long term follow‐up. Issue 2 (4th November 2020) - Cherix, Stéphane; Traverso, Aurélien; Bazan, Alexander A.; Gallusser, Nicolas; Heutschi‐Ozturk, Hafize; Abou‐Khalil, Sami; Goetti, Patrick; Letovanec, Igor; Montemurro, Michael; Bize, Pierre
Abstract: Background: Chordoma is a rare malignant tumor of the axial skeleton. Percutaneous cryoablation (PCA) is a minimally invasive technique that allows freezing of tumors under imaging control. The purpose of our retrospective study was to investigate the outcome of PCA in a selected cohort of patients with sacrococcygeal chordoma, with a minimum of 5 years follow‐up. Materials and Methods: Four patients were treated in 10 sessions. The mean follow‐up was 57.3 months. We evaluated the feasibility, the procedure‐related complications, the impact on pain control and oncological outcomes. Results: Freezing of 100% of the tumor volume was possible in 60%. Pain control was not reliably evaluable. Local recurrence occurred in 90% of the treated lesions; the mean time to progression was 8.1 months (range 1.5–16). At last follow‐up, one patient had died of the disease, one of another cause and one was receiving the best supportive care. The only patient alive without the disease had received additional carbon‐ion radiotherapy. The 5‐year survival rate after index PCA was 50%. Conclusion: Complete freezing of the tumor was technically challenging, mainly due to the complex local anatomy. Recurrence occurred in 90% of the lesions treated. PCA should be considered with caution in the curative management of sacrococcygeal chordoma.